Impact on time to active antimicrobial therapy with 24-hour pharmacist review of Accelerate Pheno BC Kit results. Issue 1 (5th August 2022) - Kinn, Patrick M.; Ford, Bradley; Percival, Kelly M.; Weiner, Lukasz; Ince, Dilek
Abstract: The Accelerate Pheno platform provides rapid identification and susceptibility data. We demonstrate successful incorporation of 24-hour pharmacist review of Accelerate Pheno results that reduced the number of patients going >3 hours from result without an order for active antimicrobial therapy from 29 (2.8%) of 1, 043 to 9 (0.85%) of 1, 053 ( P < .001).